Social media usage and its effect on Small, Medium and Micro-Enterprise performance - Gift Donga; Tendai Chimucheka; Jikijela A. N (Cita Konsultindo Research Center, 2024)
As the market environment becomes more complex, small, medium, and micro-sized businesses (SMMEs) are required to develop fresh, innovative approaches to strategically positioning themselves. Due to limited resources, it makes sense for SMMEs to adopt technologies that are relatively inexpensive, simple to use, and highly rewarding. Social media technology is useful in these situations, but little is known about how SMMEs are utilizing it, particularly in developing African economies. Therefore, the goal of this work is to empirically research the determinants of Facebook usage among SMMEs in an emerging African economy. Additionally, it looks at how Facebook usage affects SMME performance. A survey of 289 SMMEs operating in the Buffalo City Metropolitan Municipality was done to advance this discussion under the direction of a quantitative approach. According to the study results, using Facebook considerably improves SMMEs’ performance. It was also discovered that characteristics like cost effectiveness, trust, compatibility and interactivity have a positive significant impact on SMMEs usage of Facebook. The conclusions offer evidence for possible managerial and research interests and have significant practical and academic ramifications. Keywords; SMME, social media, Facebook, emerging economy